The impact of Babesia microti blood donation screening. Issue 2 (30th November 2018) - Tonnetti, Laura; Townsend, Rebecca L.; Deisting, Barbara M.; Haynes, James M.; Dodd, Roger Y.; Stramer, Susan L.
Abstract : BACKGROUND: Babesia microti, an intraerythrocytic parasite endemic in the Northeast and upper Midwest United States, is responsible for over 200 reported cases of transfusion‐transmitted babesiosis (TTB). The American Red Cross has prospectively screened donations in endemic areas for B. microti since 2012. METHODS: Blood donation samples from Massachusetts, Connecticut, Minnesota, and Wisconsin were tested by arrayed fluorescence immunoassay and real‐time polymerase chain reaction. Donors with reactive results by any test were deferred and invited to participate in a follow‐up study. RESULTS: Screening of 506, 540 donations (June 2012–May 2018) yielded 1299 reactives, 177 of which were DNA and antibody positive and 25 DNA positive only. During the same time, 23 unscreened RBC units collected in Connecticut and Massachusetts were involved in TTB cases, making the risk of transmitting the infection from an unscreened donation in these two states 15.6‐times greater than from a Babesia ‐negative unit. B. microti screening in Connecticut and Massachusetts has been associated with a reduction in TTB cases; none reported from blood donors residing in Connecticut since 2016. The positive donor rate has also decreased in Connecticut from 0.67% in 2013 to 0.23% in 2017. Ongoing follow‐up testing has shown that only 10% of antibody‐positive donors serorevert within 1 year, while 94% of polymerase chain reacton–positive donors become negative within 12 months. CONCLUSIONS: Blood donation screening for B. microti in endemic areas effectively mitigates TTB risk. Screening should be considered for all areas demonstrating ongoing risk defined as clinical cases or positive blood donors including those associated with TTB cases.